Early aggressive nutrition enhances language development in very low‐birthweight infants. Issue 6 (15th October 2014) - Shim, So‐Yeon; Ahn, Hye Mi; Cho, Su Jin; Park, Eun Ae
Abstract: Background: Inadequate nutrition in very‐low‐birthweight (VLBW) infants is known to be associated with growth failure and poor neurological outcomes. We aimed to investigate the association of early aggressive protein and energy intakes with weight gain and 18‐month neurodevelopmental outcomes in VLBW infants. Methods: A total of 90 infants among 129 infants who survived to discharge were included and divided into two groups (early aggressive nutrition [ n = 52] vs conventional nutrition [ n = 38]). Clinical findings were compared between the two groups and daily protein and energy intakes were collected for the first 4 weeks of life. Multiple regression analyses tested the association between weekly protein or energy intakes and the result of each category of the Denver Developmental Screening Test II at 18 months' corrected age or weight gain. Results: The early aggressive nutrition group had higher rates of normal language development and lower rates of growth failure (<10th percentile) at both 40 weeks' and 18 months' corrected age compared to the conventional nutrition group. After controlling for the confounding variables, higher first week protein and energy intakes each independently contributed to normal language development (odds ratio [95% confidence interval]; 9.4 [1.8–49.6] per 1 g/kg of protein increase and 1.7 [1.1–2.8] per 10 kcal/kg of energy increase). Higher first‐week protein intake was associated with a higher weight at 40 weeks' corrected age (r = 0.41, P = 0.005). Conclusions: This study demonstrates the importance of the protein and energy intakes in VLBW infants in the first week of life not only for growth but also for better language development.